Increased productivity and business management irt "kalian kripik" (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
After the idea, production machinery and equipment is the capital that a production business must have in order to run. The more complete and modern the tools and machines that produce a business then increase the business, it can further increase the business revenue. This service aims to increase the productivity and management of IRT 'You Kripik' which produces onion cakes from various original flavors from agricultural products such as potatoes, sweet potatoes and sweet potatoes. Devotion is done by providing science and technology assistance in the form of Ampia machines and Digital Scales, as well as business management training in the form of training in calculating depreciation costs, bookkeeping, and business analysis. After this service, IRT ‘You Kripik has been able to improve the quality and quality of its products. The results of devotion to produce with the help of machines and tools that are given by the Partner can improve the quality of its products, weighing materials and production results more accurately, can do business management better using bookkeeping activities, calculating depreciation and business analysis.